Knowledge and risk behavior on heaptitis c injection among the laboratory health workers in Kathmandu, Nepal. - Ghimire, Laxmi Prasad (2009)
ABSTRACT: The analytical cross-sectional study was conducted among Laboratory health workers in Kathmandu, Nepal to assess the knowledge and risk behavior on hepatitis C infection. The study was conducted by following triangular methods (face to face Interview by using pre tested semi structured questionnaire, focus group discussion by using structured guidelines and observation by using structured observation checklist). Data were collected from 160 lab health workers, among them 74 were working in government at 86 in private health centers, 3 focus group discussion and 20 observations (10 government and 10 private health centers). Data were analyzed by comparing the findings from government and private facilities. A total of 160 respondents were interviewed of which 46 percent were from government institutes and 54 percent were from private institute. Most of the respondents were male of 20-30 yrs age group and the median age of the respondents from government and private institutes were 29 yrs and 24yrs. 94 percent of the respondents were Hindu. Among total 73 percent was Lab assistant, 66 percent respondents among total respondents of government institute and 79 percent among total respondents from private institute were Lab assistants. Among total respondents from government 47 percent had 5-10 yrs experience whereas 70 percent respondents from private had working experience less than 5 yrs. Result has shown that 87 percent of the respondents had good knowledge whereas 13 percent had poor knowledge. 99 percent from government and 77 percent from private organization had good knowledge on hepatitis C. There was significant p=0.00(<0.05) association between level of knowledge and working organization. Finding from FGD also suggest that most of the respondents had good knowledge on hepatitis C. Thus knowledge level among respondents of government is higher than private institutes. Result has shown that among total respondents 33 percent had high risk behavior whereas 68 percent had low risk behavior. Among total respondents, 34 percent from government and 31 percent from private had high risk behavior. Finding from observation revealed that there was poor practice in 40 percent of government institute and in 10 percent of private institutes. The study revealed that 68 percent of the respondents who had the good knowledge, had low risk behavior and 67 percent of the respondents who had poor knowledge, also had low risk behavior. There was no significant p=0.93 (p>0.05) association between level of knowledge and risk behavior among the respondent. Policy should be implicated to change the high risk behavior of lab health workers as those who had good knowledge, session on Behavior change communication should be implicated to bring out the change in behavior. Lab health workers working in private institute are deprived of training and health education related session, there should be programme on infection prevention and health education related session especially targeted to them.